The changing image and identity of Kota Bharu, Kelantan, Malaysia: from cultural city to Islamic city / Siti Norlizaiha Harun, Zuraini Md Ali and Rodiah Zawawi - Harun, Siti Norlizaiha; Md Ali, Zuraini; Zawawi, Rodiah (Universiti Teknologi MARA, Perak, 2011)
An image of a city environment is a mental representation of external physical reality, while identity usually develops with the growth of a city through its inhabitants. The image and identity of a city can be valued in two ways of legibility: urban form and urban culture. In Malaysia, Kota Bharu, the capital city of Kelantan, known as a 'cultural city' (based on its vernacular Kelantanese Malay culture) is facing a dilemma of changing its identity into an Islamic city. This paper will discuss the past and current urban image of Kota Bharu as the capital and heart of the commercial centre in Kelantan. It will also analyse and conclude the issues and challenges of this historic town. One of the findings shows that the implementation of arch on new buildings which is inconsistent from the former identity creates conflict in sustaining its historical architectural values.